2021
DOI: 10.3389/fpubh.2021.664108
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Neutrophil to Lymphocyte Ratio in COVID-19 Patients: Still Valid in Patients That Had Started Therapy?

Abstract: COVID-19 may appear with a widely heterogeneous clinical expression. Thus, predictive markers of the outcome/progression are of paramount relevance. The neutrophil/lymphocyte ratio (NLR) has been suggested as a good predictive marker of disease severity and mortality. Accordingly, we found that NLR significantly increased in parallel with the WHO severity stage in COVID-19 patients during the Ist wave (March-May 2020; n = 49), due to the significant reduction of lymphocyte and the significant increase of neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…In the patients of the second wave (hospitalized between September 2020 and May 2021), we observed again an increase in the serum ANCAs but the serum levels of both the MPO and PR3 antigens were normal. Our data agreed with the lower number of circulating neutrophils that we observed in patients with SARS-CoV-2 infection of the second wave compared with those of the first wave and then on the lower release of cytoplasmic antigens during inflammation [5]. Thus, the increase in the ANCAs in the patients of the second wave remains unexplained.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the patients of the second wave (hospitalized between September 2020 and May 2021), we observed again an increase in the serum ANCAs but the serum levels of both the MPO and PR3 antigens were normal. Our data agreed with the lower number of circulating neutrophils that we observed in patients with SARS-CoV-2 infection of the second wave compared with those of the first wave and then on the lower release of cytoplasmic antigens during inflammation [5]. Thus, the increase in the ANCAs in the patients of the second wave remains unexplained.…”
Section: Discussionsupporting
confidence: 90%
“…Necroscopies of COVID-19 patients revealed that endothelial cell inflammation with the accumulation of lymphocytes, Viruses 2021, 13, 1718 2 of 8 plasma cells and monocytes involved several organs [3], particularly the lung [4]. In addition, circulating neutrophils, which are increased in COVID-19 patients [5], contribute to the endothelial damage by releasing tumor necrosis factor-alpha, interleukin (IL)-1 and IL-8.…”
Section: Introductionmentioning
confidence: 99%
“…Necroscopies of COVID-19 patients revealed endothelial inflammation with the accumulation of lymphocytes and monocytes in the majority of important organs [ 6 , 7 ], particularly the lungs [ 8 ]. In addition, neutrophils, which are increased in the blood [ 9 ] and tissues [ 7 ] of COVID-19 patients, may contribute to the endothelial damage and thus the release of tumor necrosis factor (TNF)-alpha, interleukin (IL)-1, and IL-8.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in comparison to the non-severe patients, pro-inflammatory cytokines and chemokines such as tumor necrosis factor (TNF)-alpha, interleukin (IL)-2, IL-6, IL-7, IL-8, IL-10, Granulocyte-colony stimulating factor(GCSF), mono cytochemoattractant protein 1 (MCP1) and macrophage inflammatory protein 1-alpha (MIP1-alpha) are often reported to be elevated in serum levels of critically ill patients ( 66 , 73 ). The elevated neutrophil-lymphocytes ratio (NLR), which is a biomarker of systemic inflammatory response syndrome, points to the devastated inflammatory state of COVID-19 patients in intensive care units ( 74 ). This hyperactive immune response along with impaired adaptive immune response may trigger pulmonary injury, ARDS, viral sepsis and organ failure as complications, and eventually death in some cases ( 74 ).…”
Section: Role Of Covid-19 In Inflammation: the Cytokine Stormmentioning
confidence: 99%
“…The elevated neutrophil-lymphocytes ratio (NLR), which is a biomarker of systemic inflammatory response syndrome, points to the devastated inflammatory state of COVID-19 patients in intensive care units ( 74 ). This hyperactive immune response along with impaired adaptive immune response may trigger pulmonary injury, ARDS, viral sepsis and organ failure as complications, and eventually death in some cases ( 74 ).…”
Section: Role Of Covid-19 In Inflammation: the Cytokine Stormmentioning
confidence: 99%